Penerapan dan Pemanfaatan E – Office Sebagai dalam Perwujudan Paperless Office - Fauzia Herdiana (Program Studi Pendidikan Administrasi perkantoran FKIP UNS, 2019)
According to (2015) in a survey he did that 55 percent of the 100 survey talent chose to be employees in the office. So it can be said that working in an office is very popular for everyone. One form of communication in offices is by correspondence or correspondence using paper. The purpose of this research is to describe e-office utilization in correspondence as a paperless office embodiment. The research used by the author is the study of literature. Literature study is a method in finding data through theoretical references that are relevant to the problems found. To create an e-office in the form of a perless office can use integra services that provide an e-office application